Mitigative effects of Eleutheroside E against the mechanical barrier dysfunction induced by soybean agglutinin in IPEC‐J2 cell line. Issue 3 (10th January 2022) - Zhao, Bao; Fan, Yueli; Li, Huijuan; Zhang, Chun; Han, Rui; Che, Dongsheng
Abstract: Soybean agglutinin (SBA) is an anti‐nutritional factor which decreases the mechanical barrier function in intestinal porcine jejunum epithelial cells (IPEC‐J2). Eleutheroside E (EE) is a key part of Acanthopanax senticosus to exert pharmacological effects. This study aims to investigate the effects of EE on the barrier function in IPEC‐J2 cells and to determine the ability of EE to enhance the protective effect of barrier function against SBA exposure. The IPEC‐J2 cells were cultured in mediums with concentration of 0.1 mg/ml EE, 0.5 ml/ml SBA and 0.1 mg/ml EE pre‐treated then treated with 0.5 mg/ml SBA. Then, the transepithelial electric resistance (TEER) value, inflammatory cytokines mRNA expression, tight junction mRNA and protein expression were tested by epithelial Voltohm meter, q‐PCR and Western blot method respectively. The results showed that cells treated with 0.1 mg/ml EE had lower permeability ( p  < 0.05) while 0.5 mg/ml SBA treatment had higher permeability through tested TEER, and higher tight junction proteins (Claudin‐3 and ZO‐1) expressions and genes (Claudin‐3, Occludin and ZO‐1) expressions ( p  < 0.05) in 0.1 mg/ml EE group. IPEC‐J2 cells pre‐treated with 0.1 mg/ml EE could significantly improve the inflammatory response caused by 0.5 mg/ml SBA by up‐regulation for IL‐10, TGF‐β, and down‐regulation gene expression of IL‐6, TNF‐α and IFN‐γ ( p  < 0.05). In conclusion, 0.1 mg/ml EE can improve the mechanical barrier function and could protect the effects while 0.5 mg/ml of SBA‐induced barrier dysfunction in IPEC‐J2.